A media strategy to spread sports awareness among Egyptian university students - mohamed algzar (International Journal of Instructional Technology and Educational Studies)
The media in its various forms is one of the most important means used in the upbringing of the individual, as it contributes to the formation of personal trends and convictions, through the dissemination of news, programs and dialogues that link the individual to the concerns and issues of his society. A media strategy through which sports awareness can be spread among Egyptian university students. This research paper also presents a number of suggestions and recommendations for spreading awareness of the importance of practicing sports activities among Egyptian university students.Research problemThrough the work of the researcher, as a specialist at the media center at Tanta University, he noticed a lack of awareness and weakness in the level of sports awareness among a large number of students, not only at the level of Tanta University, but also at the level of a large number of Egyptian university students. This appears through the participation of Tanta University in festivals and summit meetings. Such as the (Egyptian Universities Youth Week), which is at the university level in the Arab Republic of Egypt. This is what called the researcher to try to use the media field in order to contribute to spreading sports awareness among students, through research and study to reach a media strategy to spread sports awareness among university students. Egyptian.